2014
DOI: 10.1161/circulationaha.113.008115
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Autophagy for the Therapeutic Application of Histone Deacetylase Inhibitors in Ischemia/Reperfusion Heart Injury

Abstract: Editorial 1088I schemic heart disease is a leading cause of morbidity and mortality in the United States and other parts of the world. Despite therapeutic breakthroughs over the past decades such as percutaneous coronary intervention, antiplatelet and antithrombotic therapies, and angioplasty, the prevalence of ischemic heart diseases remains extremely high and constitutes a devastating factor for heart failure.1,2 Among various therapeutic strategies for ischemic heart disease, enormous efforts have been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…Occurring at the time of reperfusion of ischemic myocardium with oxygen and substrate-rich blood, reperfusion could sometimes paradoxically deteriorate heart function [2]. Anesthetics such as sevoflurane and isoflurane are reported to be valid therapeutic drugs for I/R injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Occurring at the time of reperfusion of ischemic myocardium with oxygen and substrate-rich blood, reperfusion could sometimes paradoxically deteriorate heart function [2]. Anesthetics such as sevoflurane and isoflurane are reported to be valid therapeutic drugs for I/R injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…As low levels of autophagy during ischemia and early reperfusion protect against cell death, it was suggested that spontaneous upregulation of autophagy may prevent excessive apoptosis of cardiomyocytes in response to H/R. Numerous studies have also demonstrated that autophagy is a beneficial response to ischemia/reperfusion (I/R) (21)(22)(23)(24). For example, increased autophagy was demonstrated to correlate with the functional recovery of the myocardium following I/R, and cardiac myocytes exhibiting enhanced levels of autophagy were found to be negative for apoptosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and oxidative damage have been shown to induce autophagy in cardiomyocytes [33] and are induced via the mitochondrially regulated AMPK-ULK1 signaling pathway [23]. Interestingly, autophagy seems to have a protective role in mild ischemia but can develop to be detrimental after ischemia-reperfusion [43,44]. The latter could result from the overload of autophagosome processing as well as delayed clearance of damaged organelles, resulting in increased ROS generation and cell death following MPTP opening.…”
Section: +mentioning
confidence: 99%